Establishment of new automated multi range thermal current converter - Nahed Abdelmonaem; Rasha Sayed Mohammed Ali; Hamdy Shatla (Institute of Advanced Engineering and Science, 2023)
A new automated multirange thermal current converter (TCC) has been designed and implemented at the National Institute of Standards (NIS), Egypt. Five single junction thermal current converters (SJTCCs) have been connected in parallel on PCB with an LCD, keypad and a microcontroller to control a five fast switching relays. This TCC has been designed to cover the ac current ranges from 500 mA to 5 A at frequencies from 40 Hz up to 100 kHz. The construction of the new automated TCC has been presented to solve some problems of using shunt resistance at high currents. Furthermore, a new automatic calibration system has been established to calibrate the established TCC against another standard TCC. This software program has been specially designed using MATLAB program to overcome the problems of manual calibration and measurement. The expanded uncertainties are estimated for all ranges at different frequencies and also, the ac-dc differences. The performance of the new automated TCC is also evaluated by comparing its accuracy by measuring ac currents at different frequencies with the performance of a traditional TCC.